2010
DOI: 10.4300/jgme-d-10-00114.1
|View full text |Cite
|
Sign up to set email alerts
|

Medico-Legal Education: A Pilot Curriculum to Fill the Identified Knowledge Gap

Abstract: Purpose We sought to determine if a medico-legal educational curriculum designed to increase physicians' familiarity with the legal system in a nonthreatening environment—a didactic and interactive educational seminar—would positively influence learners' knowledge base and self-awareness. Methods Because neither the Accreditation Council for Graduate Medical Education nor its Residency Review Committees specifically addresses… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 8 publications
1
10
0
Order By: Relevance
“…One striking observation in the study was the fact that almost all respondents agreed that knowledge of medico-legal principles was important in providing good healthcare to patients. This finding is consistent with a number of studies on ethical issues where participants clearly identified the link between quality health care provision and knowledge on ethics [ 14 , 15 ].…”
Section: Discussionsupporting
confidence: 91%
“…One striking observation in the study was the fact that almost all respondents agreed that knowledge of medico-legal principles was important in providing good healthcare to patients. This finding is consistent with a number of studies on ethical issues where participants clearly identified the link between quality health care provision and knowledge on ethics [ 14 , 15 ].…”
Section: Discussionsupporting
confidence: 91%
“…Our literature review for this study identified a dearth of scholarship or innovation reports on the medico‐legal aspects of privacy and confidentiality. We were heartened by some innovations in this area, including a program partnering trainee physicians with law students 24,25 as well as a 2‐day intensive medico‐legal education curriculum for residents 26 . While these innovations are distinct to single institutions, the CMPA has also recently started an annual workshop series for physicians‐in‐training reaching all Canadian medical schools 27 .…”
Section: Discussionmentioning
confidence: 99%
“…When surveyed, residents and physicians across multiple specialties reported receiving no medicolegal training at all, let alone training that is specific to documentation, and rated their knowledge as poor. 4,5,6 Emergency physicians are particularly at high risk of documentation malpractice liability due to the large number of high-risk patients and fast-paced environment. The objective of this case series was to evaluate malpractice cases related to documentation errors and practices to help improve physicians' documentation and minimize their liability risks.…”
Section: Ghaith Et Almentioning
confidence: 99%